IMAGENS DE ALTA RESOLUÇÃO ESPACIAL PARA ANÁLISE DE MEDIDAS DE DESIGUALDADE SOCIOESPACIAL. ESTUDO DE CASO: SÃO JOSÉ DOS CAMPOS - SP - Souza, Iris Marcelhas e; Alves, Claudia Durand; Kux, Hermann (Revista Brasileira de Cartografia, 2014)
The objective of this study is to measure the socio-spatial inequalities in residential areas of São José dos Campos, based on an intra-urban analysis, using QuickBird-2 satellite data. The residential space was considered to connect economic, social and political dimensions, in order to verify the corresponding stratification in space. The stratification can be observed at the configuration of different residential areas, showing the social division of space. Initially the following elements were considered in the concrete space: Size of lots, Vegetation cover, Population density, Materials of roofs, Swimming pools, Shadow, Bare Soil, Organization of blocks and lots. In this work, the establishment of a correlation among spatial differentiation elements and the living space allows to understand both the social contents and the variation of social phenomena in space. The measurement of differentiation elements was possible with QuickBird-2 image data. The Object-based Image Analysis (OBIA) concept was used for the classification of differentiation elements, while the visual analysis and data crossing was considered for others. The results obtained present the distribution of these elements and the identification of patterns in residential areas, corresponding to different spatial occupation forms by social classes. This study shows that high resolution satellite images contribute with new and relevant information about the concrete space, at intra-urban scale and it opens new possibilities for the analysis of the inequality dimension: the socio-spatial differentiation.